Optimal placement and sizing of distributed generation based on MVMO-SH - N., Md. Saad; Muhamad Zahim, Sujod; M. F., Abas; M. H., Sulaiman; Muhammad Ikram, Mohd Rashid (IET, 2018)
This paper proposes a hybrid variant mean-variance mapping optimization (MVMO-SH) algorithm to optimize distributed generation (DG) sites and sizes in the grid network. The objective function is to minimize power loss. The proposed MVMO-SH algorithm is applied on standard IEEE-30 bus test system to examine the usefulness and effectiveness of the method in solving problems related to sitting and sizing of distributed generation in transmission system. A reduction in transmission system’s total power loss and improvement in voltage profiles have been shown with appropriate sizes and sites of DG in power system network.